2000
DOI: 10.1128/jvi.74.18.8487-8493.2000
|View full text |Cite
|
Sign up to set email alerts
|

Avian Nephritis Virus (ANV) as a New Member of the Family Astroviridae and Construction of Infectious ANV cDNA

Abstract: The complete RNA genome of the avian nephritis virus (ANV) associated with acute nephritis in chickens has been molecularly cloned and sequenced. Excluding the poly(A) tail, the genome comprises 6,927 nucleotides and contains three sequential open reading frames (ORFs). The first ORF (ORF 1a) contains a sequence encoding a serine protease motif, and the second ORF (ORF 1b) has a sequence encoding an RNA-dependent RNA polymerase. ORF 1a may be linked to the second ORF by a ribosomal frameshifting mechanism. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
154
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 46 publications
3
154
0
3
Order By: Relevance
“…In guinea fowl the presence of enterovirus, observed by electron microscopy, has been associated in the past with transmissible enteritis (Pascucci & Lavazza, 1994). It is known that astroviruses are very difficult to differentiate since they share similar morphological and physiochemical features with other enteric viruses and can be misclassified (Imada et al, 2000;Guy et al, 2004). The recent detection of astrovirus in intestinal contents of diseased guinea fowl, confirmed by molecular methods (Cattoli et al 2005(Cattoli et al , 2007Canelli et al, 2009), leads us to believe that there are indeed problems related to the correct morphological identification of these enteric viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In guinea fowl the presence of enterovirus, observed by electron microscopy, has been associated in the past with transmissible enteritis (Pascucci & Lavazza, 1994). It is known that astroviruses are very difficult to differentiate since they share similar morphological and physiochemical features with other enteric viruses and can be misclassified (Imada et al, 2000;Guy et al, 2004). The recent detection of astrovirus in intestinal contents of diseased guinea fowl, confirmed by molecular methods (Cattoli et al 2005(Cattoli et al , 2007Canelli et al, 2009), leads us to believe that there are indeed problems related to the correct morphological identification of these enteric viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Since these first detections, enteritis in turkey has been increasingly associated with the presence of astroviruses (Cattoli et al, 2007;Pantin-Jackwood et al, 2007, 2008aDa Silva et al, 2008;Jindal et al, 2010a), although high astrovirus prevalence has also been reported in apparently healthy turkey flocks (PantinJackwood et al, 2007(PantinJackwood et al, , 2008aJindal et al, 2010b;Domanska-Blicharz et al, 2011). TAstV2 appears to be the most common among the identified turkey astroviruses, while TAstV1 and avian nephritis virus* an astrovirus first described as responsible for nephritis in chicken (Imada et al, 2000)*have only been detected sporadically in turkey flocks (Pantin-Jackwood et al, 2007, 2008aDomanska-Blicharz et al, 2011). In field surveys, astrovirus is a very common finding in commercial turkey farms with prevalence ranging from 84 to 100% (Pantin-Jackwood et al, 2007, 2008aJindal et al, 2010b) and from 41 to 44% (Villarreal et al, 2006;Domanska-Blicharz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ANV, originally regarded as a picornavirus, was characterized as the first astrovirus of chickens on the basis of nucleotide sequence and genome organizational similarities shared with other astroviruses (Imada et al, 2000). ANV is associated with nephritis in young chickens but infections have also been shown to cause growth depression (Shirai et al, 1991a,b).…”
Section: Discussionmentioning
confidence: 99%
“…With several exceptions, ELVs remain largely uncharacterized and unclassified. Exceptions include avian encephalomyelitis virus, a tentative member of the genus Hepatovirus (family Picornaviridae) (Marvil et al, 1999); duck hepatitis virus type 1 (DHV-1), a novel picornavirus ; another novel duck picornavirus ; and avian nephritis virus (ANV), characterized as a member of the genus Avastrovirus of the family Astroviridae (Imada et al, 2000). More recently, the characterization of a different astrovirus of chickens, named chicken astrovirus (CAstV), was reported by Baxendale & Mebatsion (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Two types of turkey astrovirus (TAstV) have been identified, TAstV-1 and TAstV-2, but these turkey astroviruses have been found to be genetically and immunologically distinct (reviewed in Koci & Schultz-Cherry, 2002). Another poultry astrovirus, avian nephritis virus (ANV) isolated from chickens by Yamaguchi et al (1979), has now been classified as an astrovirus following the complete sequencing of the viral genome (Imada et al, 2000). This virus is associated with mild growth depression and kidney lesions, and some mortality has also been reported.…”
Section: Introductionmentioning
confidence: 99%